Peningkatan Motivasi Belajar Siswa dalam Pembelajaran Microsoft Excel melalui Pembelajaran Kooperatif Tipe STAD di MAN 2 Yogyakarta - Fajar Rahmadi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This research aims to describe the application of cooperative learning using the STAD model in increasing student learning motivation at MAN 2 Yogyakarta. This research uses an action research method consisting of 4 stages, namely; planning, implementation of actions, observation and reflection. The subject of this study is class X IPS 2 students of the 2019/2020 school year with a total of 24 people, consisting of 7 male students and 17 female students. Data collection techniques use interviews, observations, documentation. The results showed that the application of STAD-type cooperative learning can improve student learning outcomes and activities in informatics subject excel materials. This can be proven by the percentage of achievements to student activity increased from 32.75% in the first cycle to 92.75% in the second cycle and can be declared successful because it has reached performance indicators.